The COVID-19 pandemic: Pathologists support the clinical infectious diseases team - Ieni, Antonio (Int J Infect Dis, 2021)
The pathologist is involved in many diagnostic steps together with the clinical infectious disease team in the management of COVID-19-affected patients. In particular, cytological and histopathological procedures as well as autoptic findings may represent useful tools to better understand the pathobiology of the disease as well as to correctly define causes of death. Moreover, pathologists have been forced to reconsider the usual laboratory workflow and introduce adequate guidelines against virus diffusion in the COVID-19 pandemic, requiring high biosafety levels.